2023
DOI: 10.1021/acsenergylett.3c00671
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Solar Batteries: Design and Device Concepts

Abstract: Solar batteries present an emerging class of devices which enable simultaneous energy conversion and energy storage in one single device. This high level of integration enables new energy storage concepts ranging from short-term solar energy buffers to light-enhanced batteries, thus opening up exciting vistas for decentralized energy storage. The dynamics of this emerging field has engendered a number of different solar battery designs, which significantly differ not only in the charge storage mechanism but al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 78 publications
(191 reference statements)
0
0
0
Order By: Relevance
“…Sumber energi alternatif ini terbarukan dan tidak berbahaya bagi lingkungan. Panel surya hanya menghasilkan energi listrik pada siang hari atau saat matahari bersinar, dimana energi listrik harus disimpan dalam baterai [2]. Bersamaan dengan kebutuhan area lokal untuk energi listrik, pengaturan yang berbeda terlihat untuk menutupi masalah dalam sel yang berorientasi matahari, dan pemeriksaan rencana pengisi daya bertenaga matahari MPPT berbasis buck converter dengan kontrol Arduino nano.…”
Section: Pendahuluanunclassified
“…Sumber energi alternatif ini terbarukan dan tidak berbahaya bagi lingkungan. Panel surya hanya menghasilkan energi listrik pada siang hari atau saat matahari bersinar, dimana energi listrik harus disimpan dalam baterai [2]. Bersamaan dengan kebutuhan area lokal untuk energi listrik, pengaturan yang berbeda terlihat untuk menutupi masalah dalam sel yang berorientasi matahari, dan pemeriksaan rencana pengisi daya bertenaga matahari MPPT berbasis buck converter dengan kontrol Arduino nano.…”
Section: Pendahuluanunclassified
“…In recent years, clean and renewable alternative energy sources have emerged with the depletion of fossil fuel reserves and the nonnegligible environmental degradation. [1][2][3][4][5] However, their intermittency and instability place higher demands on energy storage devices. Thus, developing new energy storage systems such as batteries [6][7][8][9][10] and supercapacitors [11,12] is urgent.…”
Section: Introductionmentioning
confidence: 99%
“…Advanced solar utilization technologies have been booming in recent decades to address the energy and environmental issues. , Among them, photoassisted Li-ion batteries (LIBs) hold great promise for the efficient solar energy utilization on demand. To develop attractive photoassisted LIBs, great efforts have been devoted to design the key photoelectrochemical energy storage materials for simultaneous light harvesting and energy storage . For example, researchers have found that the holes generated by lithium-rich TiO 2 under illumination can promote the deinsertion of lithium ion process and increase the capacity of the battery; nevertheless, the performance degraded significantly under prolonged light exposure .…”
Section: Introductionmentioning
confidence: 99%